Evaluasi Pelaksanaan Program Praktik Kerja Lapangan (PKL) Peserta Didik Kelas XI AKL SMK Khozinatul Ulum Todanan - Solikin, Solikin (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2022)
This study aims to 1) determine the effectiveness of the implementation of the street vendors program in the Financial Accounting Department at SMK Khozinatul Ulum Todanan in terms of the context component; 2) determine the effectiveness of the Implementation of the Street Vendors Program in the Financial Accounting Department at SMK Khozinatul Ulum Todanan in terms of the Input component; 3) determine the effectiveness of the Implementation of the Street Vendors Program in the Financial Accounting Department at SMK Khozinatul Ulum Todanan in terms of the Process component; 4) determine the effectiveness of the Implementation of the Street Vendors Program in the Financial Accounting Department at SMK Khozinatul Ulum Todanan in terms of the Product component; 5) determine the effectiveness of the Implementation of the Street Vendors Program in the Financial Accounting Department at SMK Khozinatul Ulum Todanan on context, input, process, product. The research was conducted at SMK Khozinatul Ulum Todanan. This study uses a quantitative approach and an evaluation research design. The population in this study were students, teachers, and industrial supervisors at SMK Khozinatul Ulum Todanan totaling 240 people. The research sample was determined using a simple random sampling of 151 people. Data was collected using questionnaires and documentation. Data analysis was performed by converting the raw score into a Z score (z-score) followed by a T score and then converted into the Glickman quadrant. The results showed that the implementation of the Field Work Practice (PKL) program at SMK Khozinatul Ulum Todanan in terms of context obtained effective results (+), in terms of input obtained less effective results (-), in terms of process obtained effective results (+), in terms of the product obtained effective results (+). As a whole, a joint evaluation of the implementation of the Field Work Practice (PKL) program at SMK Khozinatul Ulum Todanan in terms of context, input, process, and the product obtained effective results (+ - ++).